Activation of the B cell receptor leads to increased membrane proximity of the Igα cytoplasmic domain. - Wing-Yiu Lee; Pavel Tolar (PLoS ONE)
Binding of antigen to the B cell receptor (BCR) induces conformational changes in BCR's cytoplasmic domains that are concomitant with phosphorylation of the immunoreceptor tyrosine-based activation motifs (ITAMs). Recently, reversible folding of the CD3ε and ξ chain ITAMs into the plasma membrane has been suggested to regulate T cell receptor signaling. Here we show that the Igα and Igβ cytoplasmic domains of the BCR do not associate with plasma membrane in resting B cells. However, antigen binding and ITAM phosphorylation specifically increased membrane proximity of Igα, but not Igβ. Thus, BCR activation is accompanied by asymmetric conformational changes, possibly promoting the binding of Igα and Igβ to differently localized signaling complexes.